A Comparative Study of Blood Lactate Concentrations and Heart Rate after the Match for the Disability Challenger in Table Tennis - Muslim Mohammed Sabit; Jabbar Rahema Hassan; Meqdam Abdulkadhim Raheema (Indian Journal of Forensic Medicine & Toxicology, 2021)
Biochemical and physiological variables are among the essential scientific basics that the coach must measurein training. The research problem’s importance deals with detecting the effect of the match on the functionalstate through the concentration of lactate salts in the blood and the pulse rate—the research problem centredon the disparity in physical fitness and the appearance of signs of fatigue. With the handicapping challengeafter the match and the research aims to identify the concentration ratios of blood lactate salts and the heartrate of the disability challengers after the matches in the Paralympic Committee for the governorates ofNajaf and Diwaniyah. The researchers hypothesized that there were significant differences between theconcentration ratios of lactate salts and the heart rate between the first and second groups and in favourof the first group. The researchers used the descriptive approach using the method of comparative studies.Players were all chosen by the comprehensive inventory method to represent the research sample. They weredivided into two groups, the first representing the Paralympic Committee players for the province of Najafand the second representing the Paralympic Committee players for the province of Diwaniyah.